PENGELOLAAN PEMBELAJARAN BAHASA INGGRIS (Studi Situs SD Negeri 1 Doplang) - SUJALMO, SUJALMO (2011)
The purposes of this research is to describe the characteristics of management on listening, reading, speaking, and writing in English learning at Elementary School 1 Doplang with a single teacher system. This is a qualitative research with Ethnography design, because this design is precise to analyze social phenomena. Method of collecting data has been done by interview with informants, including key informant and other ones, observation during learning activities, and documentation, likes planning of learning activites and profile of the school. Data analyzing has been done by analyzes interactive model, consist of data reduction, data display and verification for several times until data completed. Validity for this data is tested by data triangulation (by comparing data from different sources) and methods triangulation (by comparing data from different methods). The result of this research such as are 1) teacher makes planning in order to get a clear direction by preparing planning of learning activities based on valid syllabus and curriculum so it will be accord, but lack of facilities will cause an overload occupation to the teacher. 2) reading is applied by using method of reading aloud with interesting and short text. Reading needed an ability to read correctly, including pressing and intonation in each sentence. 3) the difficulty in speaking are about comprehension on the text and also correct pronouncing. It still has lack of comprehension on the text and also to flat just like reading. 4) teacher gives a lot of exercises as training and direct practical in each learning activities. Emphasizing of exercises are focused on writing with accuracy and creativity in making statement card. Suggestion is directed especially to the teacher in order to get creativity and innovation in managing joyful, interesting and meaningful of learning activities to the students.